Darkening into Loneliness. Zdeněk Kožmín's Bubáčci - Sládek, Ondřej (Bohemica Olomucensia, 2023)
The study deals with three book collections from the diaries of the Czech literary scholar and pedagogue Zdeněk Kožmín (1925-2007). The first book, Struktury (1995), contains his diary entries from 1975-1989, i.e. from the period of normalisation when he taught at a secondary school. The second book, entitled Obtisky (1998), covers the period 1990-1997. The study also includes a reflection on the reception of Kožmín's first two books by literary critics. The core of the study is the description and analysis of the third diary, which is titled Bubáčci. It contains Kožmín's diary entries from 1998-2002. The main thematic line of the book is Kožmín's coping with the illness and death of his wife Drahomíra, and his rendering of this reality oscillates between intimate confession and testimony. The study also deals with other themes that are important to Kožmín and related to his reflection on his old age.
Keywords: Zdeněk Kožmín; Czech literary criticism; Czech literature; Diary; Old Age; Time